The seven o'clock club - Ireland, Amelia (Berkley, 2025)
"Four strangers are brought together to participate in an experimental treatment designed to heal broken hearts in this surprising and heartfelt debut novel from author Amelia Ireland. In a perfectly ordinary building, four strangers who couldn't be more different meet for the first time. Their skepticism of this new kind of grief therapy-and the unnervingly perceptive group leader-means they're all wary, but as the weeks go by, they find themselves returning again and again, pulled to work toward healing, even if it means first facing the pain head-on. A sharp-tongued lawyer who has no intention of letting down her walls, a fragile young woman looking for a place to belong, a musician at the top of his game who's one drink away from losing it all, and an interior designer facing the crumbling of her picture-perfect life-this unlikely group slowly opens up, not only to the possibility of a happier future but to friendship, change, and even romance. When a startling revelation reveals the real reason they were chosen for this group, it shakes the very foundation of what they thought they knew. What began as a journey designed to heal turns out to be a much greater test of friendship, strength, and love as they realize happiness is just outside the door...if they're brave enough to seek it."--